FARMERS’ PERCEPTIONS ON CLIMATE VARIABILITY AND CROP PRODUCTIVITY IN BILLIRI LOCAL GOVERNMENT AREA OF GOMBE STATE (FUDMA JOURNAL OF SCIENCES, 2023)
This study evaluates farmers’ perception on the impact of climate variability on cereals crops in Billiri. The study examines the causes, impacts and coping strategies of climate variability. Stratified random sampling technique was employed to determine one hundred and forty five (145) respondents. The secondary data (Rainfall) was obtained from Gombe State Agricultural Development Programme (GSADP) Ladongor station for the period of Forty (40) years. Descriptive statistics was used to analyze the data. Majority of the respondent are between the Ages of 20-49 which show they are within the active and productive age and male gender form the highest percentage of 74%. Most of the respondent has post-primary certificate. The farmers were of the opinion that temperature, dry spell and drought were increasing while soil moisture and rainfall were decreasing. The perceived impacts are poor crop yield, insufficient food supply and increase crop diseases. The respondents intensify crop diversification, planting ahead of rain (torbi), cover cropping, planting deeper than usual and planting of tolerant or improved seed variety as copping strategies. The highest amount of rainfall was observed in 1989 while the lowest amount was in 1987. The study recommended that extension worker should provide farmers with the current scientific weather information and government should provide soft loan to the farmers to expand their scale of production and to build their capacity, knowledge and response in other to enhance their resilience towards climate variability
Keywords: Farmers, Rainfall, Trend, Impact, Copping Strategies